Time to abandon routine urine analysis prior to Bacillus Calmette–Guérin administration in asymptomatic patients - Nummi, Antti; Nurminen, Pertti; Kesti, Olli; Högerman, Mikael; Ettala, Otto; Boström, Peter J.; Kaipia, Antti; Sairanen, Jukka; Järvinen, Riikka (Wiley, 2026)
Objective
This study aims to determine whether asymptomatic bacteriuria (ABU) increases the risk of infective complications requiring hospitalisation in patients undergoing Bacillus Calmette-Guérin (BCG) instillations and consequently evaluate the need to screen asymptomatic patients for bacteriuria prior to BCG administration.
Subjects/patients and methods
We analysed retrospectively all patients who received ≥1 BCG instillations as treatment of NMIBC in Helsinki University Hospital and Turku University Hospital during 2009–2018. Patients submitted urine specimens 1–7 days prior to every BCG instillation. Urine culture results and possible antibiotic prophylaxis prior to BCG administration were recorded. ABU was classified as having a positive urine culture but no dysuria or fever. All hospital admissions because of urinary tract infections and other BCG-related adverse effects within 2 weeks of BCG administration were recorded.
Results
We analysed 802 patients and 12 968 BCG instillations. ABU was recorded prior to 2428 (19%) instillations among which antibiotics were used in 527 (22%). Hospital admission was recorded after 9 (0,3%) and 39 (0,4%) instillations in the ABU and in the sterile urine groups, respectively (P = 0.9). Antibiotic prophylaxis did not affect the hospital admission rate (P = 0.2).
Conclusion
BCG instillation with ABU is safe, and the results do not support routine screening of asymptomatic patients for bacteriuria prior to intravesical BCG immunotherapy.